2007
DOI: 10.1210/jc.2006-2814
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Chemoattractant Protein-1 in Subcutaneous Abdominal Adipose Tissue: Characterization of Interstitial Concentration and Regulation of Gene Expression by Insulin

Abstract: Context:The chemokine monocyte chemoattractant protein-1 (MCP-1) is implicated in obesity-associated chronic inflammation, insulin resistance, and atherosclerosis. Objectives:The objectives of this study were to: 1) characterize the interstitial levels and the gene expression of MCP-1 in the sc abdominal adipose tissue (SCAAT), 2) elucidate the response of MCP-1 to acute hyperinsulinemia, and 3) determine the relationship between MCP-1 and arterial stiffness.Design: Nine lean (L) and nine uncomplicated obese (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
33
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 42 publications
5
33
1
3
Order By: Relevance
“…We predicted that MIP-1␣ Ϫ/Ϫ mice would have lower fasting glucose and plasma insulin concentrations based on the improved insulin and glucose tolerance observed in other genetic models of chemokine deficiency, specifically in MCP-1 Ϫ/Ϫ , CCR2 Ϫ/Ϫ , and CXCL14 Ϫ/Ϫ mice (12, 20, 30) and the fact that expression of MIP-1␣ in WAT is positively correlated with fasting plasma insulin concentrations in humans (8,19,32). However, after 16 wk on WD, male MIP-1␣ Ϫ/Ϫ and MIP-1␣ ϩ/Ϫ mice had higher fasting blood glucose levels than male MIP-1␣ ϩ/ϩ mice, and blood glucose concentrations did not differ among female mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We predicted that MIP-1␣ Ϫ/Ϫ mice would have lower fasting glucose and plasma insulin concentrations based on the improved insulin and glucose tolerance observed in other genetic models of chemokine deficiency, specifically in MCP-1 Ϫ/Ϫ , CCR2 Ϫ/Ϫ , and CXCL14 Ϫ/Ϫ mice (12, 20, 30) and the fact that expression of MIP-1␣ in WAT is positively correlated with fasting plasma insulin concentrations in humans (8,19,32). However, after 16 wk on WD, male MIP-1␣ Ϫ/Ϫ and MIP-1␣ ϩ/Ϫ mice had higher fasting blood glucose levels than male MIP-1␣ ϩ/ϩ mice, and blood glucose concentrations did not differ among female mice.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of MIP-1␣ and its receptors CCR1 and CCR5 is increased in omental and subcutaneous WAT from obese humans compared with normalweight individuals (8). Furthermore, expression of MIP-1␣ and CCR1 in WAT is positively correlated with fasting plasma insulin concentrations in humans (8,19,32). Therefore, as multiple reports have shown, WAT MIP-1␣ transcript and protein are elevated in obesity and correlated with fasting plasma insulin; however, the consequences of this have not been established.…”
mentioning
confidence: 97%
“…Westerbacka et al have demonstrated that insulin-resistant humans have increased expression of macrophage markers in AT in comparison with insulin-sensitive individuals, and that AT expression of MCP-1 and MIP-1α is elevated during hyperinsulinemic euglycemic clamps in people with insulin resistance [63]. Furthermore, a significant positive correlation has been observed between gene expression of the chemokines MCP-1, MIP-1α and MCP-2 and fasting serum insulin as well as whole-body glucose disposal rate [62]. Finally, a recent study by Stulnig and colleagues demonstrated that expression of six different chemokines and their receptors was higher in obese compared with lean subjects, and the expression of CCL3 (MIP1-α) and CCL5 (RANTES) positively correlated with fasting plasma insulin levels independent of waist circumference [64].…”
Section: Chemokinesmentioning
confidence: 98%
“…Human studies-Multiple human studies have demonstrated an elevation in gene expression of various chemokines in AT in obesity, including MCP-1, MIP-1α, MIP-1β, MCP-2, MCP-4, MIP-2α and pulmonary and activation-regulated chemokine [15,62,63]. The expression of MCP-1 from the stromal vascular fraction of fat has been shown to be greater than its expression from the adipocyte fraction, and MCP-1 expression is positively correlated with the expression of macro-phage/monocyte markers CD68 and CD14 [9], providing evidence that macrophages are the main source of this chemokine in human AT.…”
Section: Chemokinesmentioning
confidence: 99%
“…Hence, there might be differences in the inflammatory status of visceral adipose tissue in women with PCOS (36). However, it should be emphasized that the subcutaneous fat in the truncal region appears to contribute more to both the IR and the circulating NEFA pool than do adipose tissue depots elsewhere in the body (37), and it is not likely that the visceral tissue would directly account for the increased circulating concentrations of plasma cytokines and chemokines (38,39). Finally, CD11cC is not the only marker for staining M1-macrophages known in humans.…”
Section: Discussionmentioning
confidence: 99%